2007
DOI: 10.1371/journal.pone.0001304
|View full text |Cite
|
Sign up to set email alerts
|

Scrapie-Specific Pathology of Sheep Lymphoid Tissues

Abstract: Transmissible spongiform encephalopathies (TSEs) or prion diseases often result in accumulation of disease-associated PrP (PrPd) in the lymphoreticular system (LRS), specifically in association with follicular dendritic cells (FDCs) and tingible body macrophages (TBMs) of secondary follicles. We studied the effects of sheep scrapie on lymphoid tissue in tonsils and lymph nodes by light and electron microscopy. FDCs of sheep were grouped according to morphology as immature, mature or regressing. Scrapie was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 41 publications
6
35
0
Order By: Relevance
“…Subsequent studies utilizing confocal microscopy confirmed an association between PrP RES and immune cells (FDCs, tingible body macrophages, and B cells) and extended the repertoire of prion diseases with lymphoid involvement to include CWD and vCJD (42,55,60,66,67). B cells have been associated with PrP RES transport and/or deposition within the lymphoid system (9,10,18,22,23,32,43,56,64,66,81). The present study supports this contention in demonstrating that MAb 2-104 ϩ primarily B cells harvested from peripheral blood or retropharyngeal lymph nodes contain sufficient infectious prions to transmit CWD to native or transgenic hosts.…”
Section: Interval To Detection Of Cwd Infection By Tonsil Biopsymentioning
confidence: 89%
See 1 more Smart Citation
“…Subsequent studies utilizing confocal microscopy confirmed an association between PrP RES and immune cells (FDCs, tingible body macrophages, and B cells) and extended the repertoire of prion diseases with lymphoid involvement to include CWD and vCJD (42,55,60,66,67). B cells have been associated with PrP RES transport and/or deposition within the lymphoid system (9,10,18,22,23,32,43,56,64,66,81). The present study supports this contention in demonstrating that MAb 2-104 ϩ primarily B cells harvested from peripheral blood or retropharyngeal lymph nodes contain sufficient infectious prions to transmit CWD to native or transgenic hosts.…”
Section: Interval To Detection Of Cwd Infection By Tonsil Biopsymentioning
confidence: 89%
“…The presence of PrP RES in lymph node tingible body macrophages of scrapie-infected sheep (1,31,40,56) and CWD-infected deer (66) led us to investigate the possibility that circulating CD14 ϩ monocytes may contain infectious prions capable of transmitting disease. Somewhat to our surprise, the results indicated that in CWD this is not the case.…”
Section: Interval To Detection Of Cwd Infection By Tonsil Biopsymentioning
confidence: 99%
“…In fact, cellular prion protein is also expressed by B and T cells, platelets, erythrocytes, monocytes and dendritic cells with significant differences across species and in terms of the state of maturation of the cells (Aguzzi and Heikenwalder, 2005;Nuvolone et al, 2009). Recently, an ultrastructural analysis in situ with an immunogold labelling of the pathogen protein showed the presence of PrPd on both the FDC cytoplasmic extensions and the B lymphocyte membranes (McGovern and Jeffrey, 2007). Nevertheless, B lymphocytes are unlikely to represent a major site for prion replication (Montrasio et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…22 In CWD, evidence of the in vivo plasticity of the species barrier has been illustrated by successful interspecies infection of cattle, sheep, goats, ferret, mink, squirrel monkeys, transgenic mice, and recently domestic cats. 19,39 However, despite these studies, the entirety of the natural CWD host range has yet to be fully clarified. Relevant to the work described here is the potential role that sympatric species, including large cats, might play in the spread of CWD, particularly in light of studies providing compelling evidence that mountain lions ( Puma concolor ) selectively prey on CWD-infected deer.…”
mentioning
confidence: 99%